ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. P UMUR 27 TAHUN G2P1A0 DENGAN KURANG ENERGI KRONIS (KEK) DI PMB DYAH SUMARMO TANJUNGSARI BANYUDONO BOYOLALI TAHUN 2024 - Aulia Fitriani, Eliza; Hanifah, Lilik; Dewi Lieskusumastuti, Anita; Lestari, Dwi; Setyorini, Catur (Jurnal Komunikasi Kesehatan, 2025)
Maternal Mortality Rate (MMR) is one of the main indicators of the success of maternal healthprograms. Government efforts to reduce MMR and IMR by means of Sustainable DevelopmentGoals (SDGs). The role of midwives in reducing MMR and IMR so that maternal and infant healthcontinues to improve by providing comprehensive midwifery care. To provide comprehensivemidwifery care to Mrs. P aged 27 years G2P1A0 at PMB Dyah Sumarmo which includespregnancy, childbirth, postpartum, newborn care, and Family Planning (KB). ComprehensiveMidwifery Care to Mrs. P aged 27 years G2P1A0 was found to be pregnant with Chronic EnergyDeficiency (KEK). Midwifery care for delivery, spontaneous delivery was normal and there wereno complications. Postpartum midwifery care for Mrs. P was normal with no complications.Newborn midwifery care for Mrs. P was normal, female, weighing 3600 grams, and had nocomplaints. Family planning midwifery care included post-placental IUD contraception. Duringpregnancy, delivery, postpartum, newborn care, and family planning, the care met midwifery carestandards and proceeded normally.